2019
DOI: 10.1177/0956462419827673
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis in HIV infection: an update

Abstract: Psoriasis is a prevalent systemic immune-mediated disease with cutaneous manifestations. In HIV-infected patients, psoriasis may have a higher incidence, present atypical and more exuberant clinical features, and is frequently recalcitrant to treatment. Despite this aggravated severity, treatment options for psoriasis in HIV-infected individuals remain limited due to the risk of fatal immunosuppression associated with both classical immunosuppressants and new biological drugs. Notwithstanding, drug therapy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 87 publications
0
20
0
1
Order By: Relevance
“…12 T lymphocytes such as Th 17 cells, and inflammatory cytokines like TNF-α and also genetic predispositions play an important role and has been studied that activation of psoriasis causing GPP may be a result of mutations in IL-36 receptor. 10,[13][14][15] In this report, we describe a patient who has no history of psoriasis or HIV infection presenting with initially severe acute onset of pustular psoriatic lesions.…”
Section: Acute Onset Of Generalize Pustular Psoriasis In a Patient Wimentioning
confidence: 99%
See 1 more Smart Citation
“…12 T lymphocytes such as Th 17 cells, and inflammatory cytokines like TNF-α and also genetic predispositions play an important role and has been studied that activation of psoriasis causing GPP may be a result of mutations in IL-36 receptor. 10,[13][14][15] In this report, we describe a patient who has no history of psoriasis or HIV infection presenting with initially severe acute onset of pustular psoriatic lesions.…”
Section: Acute Onset Of Generalize Pustular Psoriasis In a Patient Wimentioning
confidence: 99%
“…In the patients with advanced HIV infection, even more than one type of psoriasis can be observed concurrently and this may lead to diagnostic challenges. [7][8][9][10] To the best of our knowledge, psoriasis is the result of alteration of T cells' activity which causes our treatment strategies to target the suppression of T cell hyperactivity. In contradiction with that, in HIV positive patients with decreased T-lymphocyte count, immunosuppression is generally associated with psoriasis.…”
Section: Acute Onset Of Generalize Pustular Psoriasis In a Patient Wimentioning
confidence: 99%
“…Over 80% of HIV-positive patients with psoriasis have recurrent lesions when their CD4 + lymphocyte count reaches <450. Furthermore, previous studies have reported that CD4 + counts <200 cells/mm 3 are associated with a 9-fold higher risk of clinically active psoriasis (76,77). However, the association between CD4 + lymphocyte counts and psoriasis remains controversial.…”
Section: Virusesmentioning
confidence: 99%
“…In persons living with HIV (PLHIV), dermatologic diseases are very common and may be the initial manifestation of HIV infection and are associated with significant morbidity and mortality [ 9 , 10 ]. Psoriasis has been observed throughout the course of HIV infection ranging in severity from mild to severe and may be the first presentation of HIV infection [ 11 , 12 ] and psoriatic arthritis has been described as more common and severe in these patients [ 10 ]. The prevalence of psoriasis among PLHIV has been reported to be 2–3% [ 10 , 11 , 12 ] but other studies have reported prevalence rates of 4–6% in PLHIV [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis has been observed throughout the course of HIV infection ranging in severity from mild to severe and may be the first presentation of HIV infection [ 11 , 12 ] and psoriatic arthritis has been described as more common and severe in these patients [ 10 ]. The prevalence of psoriasis among PLHIV has been reported to be 2–3% [ 10 , 11 , 12 ] but other studies have reported prevalence rates of 4–6% in PLHIV [ 11 , 13 ]. HIV infection is associated with a depletion of CD4+ lymphocytes and HIV associated psoriasis tends to present in patients with low CD4+ cell counts and an overall reduced immune status [ 14 ].…”
Section: Introductionmentioning
confidence: 99%